Robust Optimal Planning and Operation of Electrical Energy Systems - Mohammadi-ivatloo, Behnam; Nazari-Heris, Morteza (Springer International Publishing : Imprint: Springer, 2019)
This book discusses the recent developments in robust optimization (RO) and information gap design theory (IGDT) methods and their application for the optimal planning and operation of electric energy systems. Chapters cover both theoretical background and applications to address common uncertainty factors such as load variation, power market price, and power generation of renewable energy sources. Case studies with real-world applications are included to help undergraduate and graduate students, researchers and engineers solve robust power and energy optimization problems and provide effective and promising solutions for the robust planning and operation of electric energy systems.